Salivary Trefoil Factor (TFF3) in Stage I–II Periodontitis: A Prospective Clinical Study - Palwankar, Pooja; Verma, Ritika; Pandey, Ruchi; Goyal, Anjana (European Journal of General Dentistry, 2023)
Objective This article evaluates the salivary trefoil factor levels using enzyme-linked immunosorbent assay and clinical parameters in stage I to II periodontitis subjects.Materials and Method A total of 44 subjects with periodontitis and healthy periodontium were enrolled for the study as per the inclusion criteria. The subjects were selected and categorized as group A (control group) and group B (test group). Scaling was performed on healthy subjects at baseline and 1 month if necessary and scaling and root planing was performed for periodontitis subjects. Trefoil factor 3 (TFF3) levels was analyzed at first and post-nonsurgical periodontal therapy followed by clinical parameters, respectively.Statistical Analysis Inferential statistics were performed using independent t-test and repeated measures of analysis of variance (ANOVA) test. Independent t-test was used for the intergroup comparison of all the variables. Repeated measures of ANOVA test along with post hoc Bonferroni test was used for the intragroup comparison and the level of statistical significance was set at 0.001.Results Difference in TFF3 levels and clinical parameters was seen between groups A and B, which was statistically significant.Conclusion Within the constraints of the study, it can be stated that TFF3 is a relevant biomarker to determine the activity and association of periodontal and systemic diseases, gastrointestinal disorders, and inflammatory bowel diseases.
Keywords: trefoil factor; periodontitis; biomarker; ELISA; TFF3; TFF1; TFF2; SRP; NSPT